Glucose Deprivation Enhances the Antiproliferative Effects of Oral Hypoglycemic Biguanides in Different Molecular Subtypes of Breast Cancer: an in Vitro Study - Bardaweel Sanaa K.; Alsalamat Husam A.; Aleidi Shereen M.; Bashatwah Rasha M. (Acta Pharmaceutica)
Extensive in vitro studies have been conducted to evaluate the anticancer activity of oral hypoglycemic agents. Many of these studies experienced detrimental limitations, since they were conducted on cancer cells commonly grown in culture media consisting of extremely high concentrations of growth factors and glucose. The present study was aimed at exploring the antiproliferative effects of the commonly studied metformin and the less frequently reported phenformin oral hypoglycemic agents on different molecular subtypes of breast cancer under rich glucose and glucose deprived conditions. Our results indicate that under glucose deprived conditions, which better reflect the factual glucose-starved solid tumors in vivo, biguanides exert more antiproliferative activities against the three molecular subtypes of breast cancer cell lines examined in this study. In addition, the observed antiproliferative activities of biguanides appear to be mediated by apoptosis induction in breast cancer cells. This induction is significantly augmented under glucose deprived conditions.